How the Medium is the Message - Biondi, Zach (New Explorations)

(untitled) (New Explorations Association, 2025)
In Understanding Media, Marshall McLuhan says “the medium is the message.” The phrase became famous and then cliche. Today, the proliferating texts about the effects of social media, the internet, and smartphones are, for better or worse, a series of footnotes to McLuhan. Authors often parrot McLuhan more than they intend, and the philosophical work does not extend far beyond his initial insight. While some question McLuhan’s skills as a philosopher, given his enduring importance, the paper aims to interpret and evaluate McLuhan’s seminal claim from a philosophical perspective. It outlines the core meaning of ‘the medium is the message’; discusses McLuhan’s claim that the message of the medium is, in some sense, more important than the content the medium conveys; and, finally, considers whether the effects of a medium are good or bad.